All-in-one in situ colorimetric RT-LAMP assay for point-of-care testing of SARS-CoV-2. Issue 19 (10th September 2021) - He, Yugan; Wang, Liqin; An, Xiaoping; Tong, Yigang
Abstract : A facile all-in-one nucleic acid testing assay by combining Si-OH activated glass bead-based viral RNA fast extraction and in situ colorimetric reverse transcription loop-mediated isothermal amplification detection in a single tube was developed. Abstract : The ongoing outbreaks of the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have resulted in unprecedented challenges to global health. To effectively contain the COVID-19 transmission, rapid tests for detecting existing SARS-CoV-2 infections and assessing virus spread are critical. To address the huge need for ever-increasing tests, we developed a facile all-in-one nucleic acid testing assay by combining Si-OH activated glass bead (aGB)-based viral RNA fast extraction and in situ colorimetric reverse transcription loop-mediated isothermal amplification (RT-LAMP) detection in a single tube. aGBs demonstrate a strong ability to capture viral RNA in a guanidinium-based lysis buffer, and the purified aGBs/RNA composite, without RNA elution step, could be directly used to perform RT-LAMP assay. The assay was well characterized by using a novel SARS-CoV-2-like coronavirus GX/P2V, and showed a limit of detection (LOD) of 15 copies per μL in simulated clinical samples within 50 min. We further demonstrated our assay by testing simulated SARS-CoV-2 pseudovirus samples, showing an LOD of 32 copies per μL and high specificity without cross-reactivity with the most closely related GX/P2V or host DNA/RNA. The all-in-one approach developed in this study has the potential as a simple, scalable, and time-saving alternative for point-of-care testing of SARS-CoV-2 in low-income regions, as well as a promising tool for at-home testing.